Addressing the needs of Canadians with rare diseases: an evaluation of orphan drug incentives. Issue 3 (31st August 2018) - Harris, Emily
ABSTRACT: It is uncertain whether a Canadian orphan drug policy, similar to those used in the US and EU, will be given further consideration. The justification for having an orphan drug policy is initially discussed, with this article proceeding on the basis that morality and a commitment to equality validate providing some form of orphan drug incentive(s) in Canada. That being said, it is unclear how 'orphan drug' should be defined and, accordingly, how incentives should be allocated. Three pharmaceutical industry incentives are then evaluated in order to identify how the needs of patients with rare diseases can be addressed. Market exclusivity has effectively encouraged investment in orphan drugs and therefore it is recommended that the incentive be implemented in Canada. Priority review voucher programs are still in their infancy, making it difficult to draw strong conclusions about these programs. Introducing a voucher program in Canada is nevertheless not recommended because priority review in Canada is unlikely to be sufficiently valuable. An orphan drug-specific tax credit offers a convenient means of subsidizing orphan drug development without being overly costly, given the narrow parameters within which the credit would operate. Therefore, a Canadian orphan drug tax credit is also recommended.